Magic mirror using kinect - Anika Binte Habib; Asad, Adnan; Wasiq Bin Omar (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.